Hubungan antara Konsep Diri Sosial, Persepsi Siswa tentang Dukungan Sosial Orangtua, dan Teman Sebaya dengan Komunikasi Interpersonal Siswa dan Implikasinya terhadap Pelayanan Bimbingan dan Konseli - Astarini, Dilla; Nirwana, Herman; Ahmad, Riska (Konselor, 2016)
This research background is the low skilled interpersonal communication from student. Social self-concept, student perception regarding parents social support, and peer social support are factors suspected influence student interpersonal communication. This research is aimed to describe and examined: (1) relationship between social self-concept, student perception regarding parents social support, and peer social support with interpersonal communication; (2) together relationship between social self-concept, student perception regarding parents social support, and peer social support with interpersonal communication. This research used quantitative approach by using descriptive correlational method. The population of this research were 670 students of MTsN Parak Lawas Padang. The sample were 251 students that were chosen by using Proportional Stratified Random Sampling. The instrument that had is the scale by using the Likert scale model. The data research was analize by descriptive statistics, simple, and multiple regression. This discover research show: (1) there was a relationship between social self-concept, student perception regarding parents social support, and peer social support with interpersonal communication; (2) there was together a relationship between social self-concept, student perception regarding parents social support, and peer social support with interpersonal communication.